The Analysis of Creativity and Misconceptions of Elementary School Student Teachers in Science Learning through the Mind Map in Virtual Classrooms - Nur Inayah Syar (Al Ibtida: Jurnal Pendidikan Guru MI, 2022)
AbstractThis research aimed at assessing the student teachersâ€™ creativity and detecting their misconceptions about the material of Organism Reproduction. This descriptive research involved a total of 28 students of MI/elementary school student teachers. The Mind Map was used as a tool to assess the students' creativity and misconceptions. The data were then analyzed descriptively with scoring techniques based on the Creative Mind Map Rubric. The creativity assessment was categorized into four aspects including fluency, flexibility, originality, and elaboration. Of these four aspects, the highest level of achievement was on the fluency aspect (60.72%). Meanwhile, the lowest level of achievement was on the originality aspect (3.57%). The category of studentsâ€™ creativity was â€œAlmost Not Creativeâ€ with the percentage of 39.29%. It means that on average each student only acquired one to two aspects of creativity. The studentsâ€™ misconceptions were detected almost in each sub material of Organism Reproduction. However the highest number of misconceptions was found in the material of Animal Reproduction, 21 times on the generative reproduction of vertebrates and invertebraes animals. This study provided an evaluation of alternative instruments to measure the studentsâ€™ creativity and misconceptions in science learning.Keywords: mind map, creativity, misconception, virtual classrooms.Â AbstrakPenelitian ini bertujuan untuk menilai kreativitas mahasiswa calon guru dan mendeteksi miskonsepsi mereka pada materi Perkembangbiakan Makhluk Hidup. Penelitian deskriptif ini melibatkan 28 orang mahasiswa calon guru MI/SD. Mind map digunakan sebagai alat untuk menilai kreativitas dan miskonsepsi mahasiswa. Data kemudian dianalisis secara deskriptif dengan teknik penskoran berdasarkan creative mind map rubric. Penilaian kreativitas dibagi menjadi empat aspek, yaitu fluency, flexibility, originality dan elaboration. Dari keempat aspek tersebut fluency memiliki tingkat ketercapaian yang paling tinggi (60,72%). Sementara itu, aspek terendah adalah originality (3,57%). Tingkat kreativitas mahasiswa berada pada kategori â€œalmost not creativeâ€ dengan persentase 39,29%. Ini berarti bahwa rata-rata setiap mahasiswa hanya menguasai satu hingga dua aspek kreativitas. Miskonsepsi mahasiswa terdeteksi hampir di setiap sub materi Perkembangbiakan Makhluk Hidup. Namun demikian, jumlah miskonsepsi tertinggi ditemukan pada sub materi Perkembangbiakan Hewan, yaitu sebanyak 21 kali pada konsep perkembangbiakan generatif mengenai hewan vertebrata dan invertebrata. Penelitian ini memberikan alternatif instrumen evaluasi yang mampu mengukur kreativitas serta miskonspsi mahasiswa pada pembelajaran IPA.Kata kunci: mind map, kreativitas, miskonsepsi, kelas virtual.